2011
DOI: 10.1097/mpg.0b013e3182144c74
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of VEGF and TGF‐β1 During Exclusive Enteral Nutrition in IBD

Abstract: Different effectiveness of EEN in achieving remission in CD and UC may result from a modification of growth factor production. EEN stimulated TGF-β1 production in CD but not in UC, which possibly resulted in higher effectiveness of EEN in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
1
28
0
2
Order By: Relevance
“…They found that TGF-B1 was significantly higher in patients with crohn's disease in remission than in active disease (47, 48, and 49). In another study, Wedrychowicz et al assessed the influence of exclusive enteral nutrition on serum concentration of TGF-B1 and vascular endothelial growth factor (VEGF) in 24 patients with crohn's disease and 15 patients with ulcerative colitis; they found increased serum TGF-B1 in ulcerative colitis patients versus the crohn's disease group and controls (50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that TGF-B1 was significantly higher in patients with crohn's disease in remission than in active disease (47, 48, and 49). In another study, Wedrychowicz et al assessed the influence of exclusive enteral nutrition on serum concentration of TGF-B1 and vascular endothelial growth factor (VEGF) in 24 patients with crohn's disease and 15 patients with ulcerative colitis; they found increased serum TGF-B1 in ulcerative colitis patients versus the crohn's disease group and controls (50).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies (1,50), graded ulcerative colitis patients according to the Rachmilewitz Clinical Activity Index only and the Endoscopic Activity Index did not follow this score.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Sturm et al 35 reported serum values of TGF-β1 that did not differ between patients with UC and healthy controls. However, the patient characteristics in this study differ from those of Wedrychowicz et al 34 and Sambuelli et al, 36 in that Sturm et al 35 did not assess patients pre-and posttreatment, but rather, measured TGF-β1 in a cross-sectional sample of patients who would be assumed to be on ongoing therapy (although this is not specifically stated in the manuscript). While the disease activity of their patient group was spread over mild (n=12), moderate (n=8), and severe disease (n=9), it may be that TGF-β1 levels were reflective of ongoing therapy, and therefore, were consistent with normal values.…”
mentioning
confidence: 78%
“…With respect to enteral and parenteral nutrition for achieving or maintaining remission in UC, the evidence is also unsupportive in this respect, and existing guidelines do not recommend their use in this manner. 23,33 According to Wedrychowicz et al, 34 a possible mechanism for the ineffectiveness of enteral nutrition has to do with modification of growth factor production, notably stimulation of transforming growth factor β1 (TGF-β1), which these authors reported occurs in patients with Crohn's disease in …”
mentioning
confidence: 99%
See 1 more Smart Citation